A N-terminal truncated intracellular isoform of matrix metalloproteinase-2 impairs contractility of mouse myocardium - Lovett, David H. (Frontiers Media S.A., 2014)
The full-length isoform of matrixmetalloproteinase-2 (FL-MMP-2) plays a role in turnover of the cardiac extracellular matrix. FL-MMP-2 is also present intracellularly in association with sarcomeres and, in the setting of oxidative stress, cleaves myofilament proteins with resultant impaired contractility. Recently, a novel N-terminal truncated MMP-2 isoform (NTT-MMP-2) generated during oxidative stress was identified and shown to induce severe systolic failure; however, the injury mechanisms remained unclear. In this study, cardiac-specific NTT-MMP-2 transgenic mice were used to determine the physiological effects of NTT-MMP-2 on: force development of intact myocardium; the function of cardiac myofilaments in demembranated myocardium; and on intracellular Ca(2+) transients in isolated myocytes. We related the contractile defects arising from NTT-MMP-2 expression to the known intracellular locations of NTT-MMP-2 determined using immunohistochemistry. Comparison was made with the pathophysiology arising from cardiac-specific FL-MMP-2 transgenic mice. Consistent with previous studies, FL-MMP-2 was localized to myofilaments, while NTT-MMP-2 was concentrated within subsarcolemmal mitochondria and to sites in register with the Z-line. NTT-MMP-2 expression caused a 50% reduction of force development by intact myocardium. However, NTT-MMP-2 expression did not reduce myofilament force development, consistent with the lack of NTT-MMP-2 localization to myofilaments. NTT-MMP-2 expression caused a 50% reduction in the amplitude of Ca(2+) transients, indicating impaired activation. Conclusions: Unlike FL-MMP-2, NTT-MMP-2 does not mediate myofilament damage. Instead, NTT-MMP-2 causes impaired myocyte activation, which may involve effects due to localization in mitochondria and/or to transverse tubules affecting Ca(2+) transients. Thus, FL-MMP-2 and NTT-MMP-2 have discrete intracellular locations and mediate different intracellular damage to cardiac myocytes.